A self-report survey on Pentecostal Christianity as a restraining factor of crime in Mankweng Area - Sebake, Julian Raaphahle (My University, 2020)
The purpose of this study was to determine the strength of Pentecostal Christianity and its practices in restraining followers from committing crime focusing on the individuals’ criminality prior to, in the different growth stages (before being born again, being born-again and being Spirit-filled) of their spiritual lives and the length of time practising the belief. The present study aimed at determining whether Pentecostal Christianity has a restraining influence on Christians from committing crime. A quantitative, explanatory study was conducted to statistically analyse the strength of Pentecostal Christianity in restraining Christians from committing crime. Data were collected through administration of questionnaires in three Pentecostal churches in the Mankweng Area on different Sundays. Data were further analysed using SPSS statistical program where inferential statistics was used to test hypotheses using the Kruskal-Wallis test in conjunction with Chi-Square test of independence and descriptive statistics were also used to formulate graphs to present findings. The hypotheses tested showed a significant difference in criminality before being born again, after being born-again and baptism in the Holy Spirit with a p value of less than 0,.05. The length an individual has practising the faith has no significant difference in reducing criminal behaviour. This study concluded that the Pentecostal Christian faith, to some extent, deters followers from committing crime. Keywords: Christianity, Pentecostal Christianity, crime
Thesis (M. A. (Criminology)) -- University of Limpopo, 2020
Keywords: Christianity; Pentecostal Christianity; Crime; Crime -- Religious aspects -- Christianity; Crime -- South Africa -- Limpopo